Synthesis, Photophysical, Solvatochromic and DFT Studies of Newer 1-(2-(naphthalen-2-yl)-2-oxoethyl) pyridin-1-ium bromide - Atul S. Patil; Raosaheb S. Patil (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
A newer pyridinium compound was synthesized under microwave irradiation by reaction of pyridine and 2-bromo-1-(naphthalen-2-yl)ethanone. The pyridinium compound was characterized by mass, IR, 1H NMR, 13C NMR spectral analysis, also photophysical, solvatochromic, and thermal properties of newer pyridinium compound were investigated. Solvent dependent optical properties of pyridinium compound with range of solvents with varying polaritieswere studied using Lippert-Mataga plot and solvent polarity empirical parameter ET(30). The thermal stability and phase behavior were studied by TGA and DSC analysis at a heating rate of 10 deg min-1. DFT computation was performed to get the optimized molecular orbitals and HOMO - LUMO energies.